Financiamento da Política de Assistência Social em municípios sergipanos: análise sobre os reflexos do estado ultraneoliberal (2017-2022) - Dória, André Luiz Novais (2024)
This dissertation aims to understand the emerging tensions in the financing of Social Assistance Policy in Brazil between 2017 and 2022, in a context of attacks from the ultraneoliberal agenda, which reifies the anti-humanist hegemonic project and destroys social rights achieved in the 1988 Federal Constitution. The National Social Assistance Policy (PNAS) of 2004 and the Unified Social Assistance System (SUAS) stand out as significant achievements threatened by defunding. The foundations and dynamics of political economy are examined from a critical Marxist perspective, focusing on the transformations of capitalism from its competitive phase to monopolistic capitalism. The accumulation crises and the phenomenon of financialization are analyzed, highlighting the transition of capitalism to ultraneoliberalism in Brazil and its economic and social implications. The global economic crises, such as the subprime crisis of 2008, and their reverberations in the national scenario are highlighted. It traces the historical evolution of social assistance in Brazil, from its charitable roots to its consolidation as a social right in the 1988 Constitution. The relationship between economic development, political transformations, and social practices that shaped social assistance is explored. The Constitutional Amendment nº 95, which restricted the financial resources available for social assistance, causing service precariousness and hindering the inclusion of new families in social programs, is highlighted. Focusing on the direct impacts of Constitutional Amendment nº 95, it analyzes how budgetary restrictions affected the Social Assistance Policy in four municipalities in Sergipe: Areia Branca, Poço Redondo, São Cristóvão, and Aracaju. Empirical research reveals local strategies to mitigate the effects of spending freezes and the difficulties faced in adapting to new fiscal conditions. The results demonstrate a declining trend in transfers from the National Social Assistance Fund (FNAS), hindering the effective planning and execution of social assistance services. The analyzed data indicate a continuous reduction in federal transfers for Basic Social Protection (PSB) and Special Social Protection (PSE), with budget forecasts often exceeding the amounts actually transferred. This defunding compromises the municipalities' capacity to meet the needs of the vulnerable population. The dissertation highlights the need for structural revisions in social assistance financing to ensure the sustainability and effectiveness of the services provided. This dissertation contributes to the understanding of the challenges and possibilities for strengthening the Social Assistance Policy in Brazil, emphasizing the importance of robust and sustainable financing for social protection and the promotion of social justice.